2003
DOI: 10.1038/sj.onc.1206573
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional silencing of the DLC-1 tumor suppressor gene by epigenetic mechanism in gastric cancer cells

Abstract: Southern analysis showed that seven of nine human gastric cancer cell lines did not express DLC-1 mRNA, but contained the DLC-1 gene. To identify the mechanism of the loss of DLC-1 mRNA expression in these cell lines, we investigated the methylation status of DLC-1 gene by using methylation-specific PCR (MSP) and Southern blot, and found that five of seven DLC-1 nonexpressing gastric cancer cell lines were methylated in the DLC-1 CpG island. Treatment with 5-aza-2 0 -deoxycytidine (5-Aza-dC) induced DLC-1 mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
86
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 38 publications
6
86
0
Order By: Relevance
“…We also showed that DLC1 functions as a TSG in NPC and esophageal carcinoma cells. As DLC1 methylation has not been reported in these three tumors before, our results add more candidates to the reported list of cancers (liver, breast, colon, gastric, lung and prostate) with epigenetic abnormalities of this TSG (Kim et al, 2003;Plaumann et al, 2003;Wong et al, 2003;Yuan et al, 2003aYuan et al, , b, 2004. Interestingly, in one of our independent studies screening for downregulated genes in NPC cell lines using whole-genomic microarray expression profiling combined with pharmacologic demethylation, DLC1 was also identified as one of the downregulated target genes (Tao et al, manuscript in preparation).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…We also showed that DLC1 functions as a TSG in NPC and esophageal carcinoma cells. As DLC1 methylation has not been reported in these three tumors before, our results add more candidates to the reported list of cancers (liver, breast, colon, gastric, lung and prostate) with epigenetic abnormalities of this TSG (Kim et al, 2003;Plaumann et al, 2003;Wong et al, 2003;Yuan et al, 2003aYuan et al, , b, 2004. Interestingly, in one of our independent studies screening for downregulated genes in NPC cell lines using whole-genomic microarray expression profiling combined with pharmacologic demethylation, DLC1 was also identified as one of the downregulated target genes (Tao et al, manuscript in preparation).…”
Section: Discussionsupporting
confidence: 66%
“…DLC1 was reported to be a functional TSG frequently inactivated by promoter methylation in multiple carcinomas (Kim et al, 2003;Plaumann et al, 2003;Wong et al, 2003;Yuan et al, 2003aYuan et al, , b, 2004. DLC1 is located at 8p22 -a region where we also detected heterozygous deletion in some esophageal cell lines by conventional CGH (Tang et al, 2001), but no study of DLC1 has been performed in esophageal carcinoma yet.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, DNA methylation and the chromatin condensation of integrin aL were detected in fibroblasts, and were suggested to contribute to the tissue-specific expression of integrin aL (Akama et al, 1997;Lu et al, 2002). Previously, we reported that DNA methylation is one of the predominant mechanisms for inactivating various genes, like, TGF-b type I receptor, TIMP-3, p16, COX-2 and DLC-1, during gastric carcinogenesis (Kang et al, 1999;Kang et al, 2000;Song et al, 2000Song et al, , 2001Kim et al, 2003). These findings led us to investigate whether integrin a4 expression could be regulated by DNA methylation, because integrin a4 expression is very low in our gastric carcinoma cells (Figure 1a).…”
Section: Discussionmentioning
confidence: 99%
“…5 The promoter hypermethylation of multiple tumor suppressor genes resulting in gene silencing has been recognized as an important mechanism in gastrointestinal carcinogenesis. [6][7][8][9][10][11][12][13][14][15] In a previous study, TSPYL5 was identified as one of the genes induced after treatment with DNA methylation and histone deacetylation inhibitors in glioma cell lines using microarray analysis. 16 The TSPYL5 showed a high frequency of DNA methylation-mediated silencing in both glioma cell lines and primary glial tumors.…”
mentioning
confidence: 99%